Wajah Multukuralisme Islam yang Tersingkirkan (Analisis Struktural Fungsional Kurikulum Mata Pelajaran Sosiologi Pada Madrasah) - Miftahusyai`an, Mohammad (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
This study examined behavioral approach in dealing with studentsâindiscipline behavior at SMP Diponegoro Depok Sleman Yogyakarta whose familybackground of divorce. Qualitative descriptive methodwas applied to reveal the abovephenomenon and the data were collected by observation and in-depth interview. Itrevealed that there were three main steps in applying this behavior approach. Firstly,assessment was essentially conducted in advance to investigate the underlying factorswhich cause indiscipline to happen. The second step was a goal setting; discussing withstudents about the consequences that might be faced when they engage in undisciplinedbehavior. At this stage, the researcher along with the students had succeeded in devisinga plan to solve the problem. The last stage was that carrying out the research to assessstudents followed by counseling contract, relaxation, modeling, reward and punishment,encouragement, time-out, home assignment and ending with the evaluation phase. Theresults found that behavioral technique was one of effective approaches in guidanceand counseling to handle maladaptive on adaptive behavior, and this approach wasvery appropriate to handle undisciplined students in school.Ø§ÙÙØ¯Ù Ø§ÙØ±Ø¦ÙØ³Ù ÙÙ ØªØ¹ÙÙÙ ØªØ¹Ø¯Ø¯ÙØ© Ø§ÙØ«ÙØ§ÙØ§Øª Ø¹Ù Ø·Ø±ÙÙ ØªØ¹ÙÙÙ ÙØ§Ø¯Ø© Ø¹ÙÙ Ø§ÙØ§Ø¬ØªÙØ§Ø¹ ÙÙ Ø§ÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§ÙÙØ©ÙÙ Ø¥Ø¹Ø¯Ø§Ø¯ Ø§ÙØ·ÙØ§Ø¨ ÙÙØ¹ÙØ´ÙØ§ Ø¨ÙÙ Ø§ÙÙØ¬ØªÙØ¹ ÙØªØ±Ø§ØÙÙÙ ÙÙÙØ§ Ø¨ÙÙÙÙ Ø·Ø¨ÙØ§ ÙÙÙÙÙ ÙÙ Ø¨ÙØªØ´Ø§Ø³ÙÙØ§. ÙØ¥Ù ØØ§ÙØ© ÙØ¬ØªÙØ¹ÙÙØ¬ÙØ¯Ø© ÙØ§ÙÙØ±ÙÙÙÙ ÙÙÙØ§ ÙØ¹ØªÙØ¯ÙÙ Ø¨Ù ÙÙ Ø§ÙØ£Ø¯ÙØ§ÙØ ÙÙØ°Ø§ Ø§ÙØ£ÙØ± Ø¨Ø¶Ø§Ø¹Ø© ÙØ§Ø¨Ø¯ ÙÙ Ø§Ø«Ø¨Ø§ØªÙØ§ ÙÙ ÙÙÙØ³ÙÙ. ÙØ§ÙÙØ§ÙØ¹ Ø¥Ù ØªØ¹ÙÙÙØ¹ÙÙ Ø§ÙØ§Ø¬ØªÙØ§Ø¹ ÙÙ Ø§ÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØ¶ÙØ¹ ÙÙÙ Ø±ÙØÙ. ÙØ£ØµØ¨Ø ØªØ¹ÙÙÙ ÙØ°Ù Ø§ÙÙØ§Ø¯Ø© Ø¹ÙØ¨Ø¦Ø§ Ø¬Ø¹Ù Ø§ÙÙÙÙØ¬ Ø§ÙØ¯Ø±Ø§Ø³ÙÙØ³ÙÙÙØ§ ÙØ£ØµØ¨ØØª Ø§ÙÙØ§Ø¯Ø© ÙØ¬ÙÙØ© ÙÙ Ø³Ø·ÙØ± ÙÙÙÙØ§ Ø£ØµØ¨ØØª ÙØ§Ø¯Ø© ÙØ¯ÙÙØ© ØÙÙ Ø¹ÙÙÙØ§ Ø§ÙÙØ¯Ø±Ø³ ÙØÙ Ø§ÙØ·ÙØ§Ø¨. ÙØ°Ø§ÙØ¥ÙÙ ÙÙÙ ÙÙÙØ¯Ø±Ø³ Ø¬Ø¹Ù Ø§ÙÙÙÙÙÙ ÙÙ â ÙÙÙ Ø¨ÙØ§Ø¡ Ø§ÙØªÙØ§ØµÙØ§Øª Ø§ÙØ§Ø¬ØªÙØ§Ø¹ÙØ© â Ø§ÙÙØ³Ø§Ø¹Ø¯Ø© ÙÙ ÙÙ Ø£Ø¯Ø§Ø¡ Ø¹ÙÙÙ. ÙÙÙØ§ÙÙØ¨ØºÙ â Ø¹ÙÙ Ø§ÙÙØ¯Ø±Ø³ â Ø§ÙÙÙØ§Ù Ø¨Ù : 1( Ø¨Ø¯Ø£ Ø§ÙÙØ¯Ø±Ø³ ÙØ¨ØØ« Ø¹Ù Ø´ÙÙ Ø§ÙØ¹ÙØ§ÙØ© Ø§ÙÙÙÙØ© ÙØ§ÙÙØ±ÙØ¨Ø© Ø¨ÙÙ ÙÙ Ø¨ÙØ¦Ø©Ø§ÙÙØ¯Ø±Ø³Ø©. ÙØ°Ù Ø§ÙØ¹ÙØ§ÙØ© ÙÙÙÙ Ø£Ù ØªÙÙÙ ÙÙ Ø´Ø¨ÙØ§Øª Ø§Ø¬ØªÙØ§Ø¹ÙØ© ÙØªØ¬Ø§ÙØ³Ø©Ø 2( ØØ§ÙÙ Ø§ÙÙØ¯Ø±Ø³ Ø§ÙØØµÙÙ Ø¹ÙÙ Ø´ÙÙØ§ÙØªÙØ§ØµÙ Ø§ÙØ§Ø¬ØªÙØ§Ø¹Ù Ø§ÙÙØªÙØªÙØ ÙØ§ÙÙÙØ³ÙØ¹ ÙØ¹ÙÙ Ø§ÙØ¬ÙÙØ¹. ÙØ°Ù Ø§ÙØªÙØ§ØµÙØ§Øª ÙÙÙÙ Ø£Ù ØªÙÙÙ ÙÙ Ø´Ø¨ÙØ§Øª Ø§Ø¬ØªÙØ§Ø¹ÙØ© ÙØªÙÙÙØ¹Ø©